Estrategias de Afrontamiento que Implementaron las Mujeres con Doble Presencia para Salvaguardar su Bienestar Psicológico durante la Modalidad de Trabajo Remoto - Aguilar Calderón, Alejandra; Rozo Gómez, Jeimy Stefany (Universidad Antonio Nariño, 2022)
In the interest of understanding the most significant problems that have been generated due to the health emergency by Covid19, the following investigation sought to analyze what were the coping strategies implemented by women with double presence to safe psychological wellguard their being during the modality of remote work. For this, the study was carried out with the collaboration and participation of 4 females between the ages of 28 and 35 from the city of Bogotá, who performed their role as mothers an that is, from home. d professionals in the same space and time, This investigative study corresponded to a methodological design with a qualitative descriptive scope and a phenomenological approach, so that, based on the narratives offered by the participa nts, it will be possible to obtain a greater analysis and identification of the different forms or coping strategies that these women had to deal with the possible work or personal changes in which they were immersed. The respective analysis of the narrati ons, derived from the open and unstructured interviews, was carried out based on the main postulates on the subject, which were detailed and related in the theoretical framework of this research work, psychosocial factor , psychological welland thus, categorized into 3 parts: being and coping strategies. Now, regarding the results obtained, it is suggested that for dealing with the psychosocial risk situations that they experienced during the remote work modality, there is variety of coping strategies that were implemented depending on the level of demand, family and individual resources, the age and level of schooling of their children and finally, the motivations at a personal/ professional level